Molecular mechanisms of intestinal damage in COVID-19 (literature review) - O.A. Levashova; T.I. Dolgikh; O.N. Lesina; V.G. Mineeva; N.I. Mikulyak (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2023)
Many patients with COVID-19 have gastrointestinal symptoms and diarrhea is of the most common ones. To date, there is no consensus about the mechanisms of COVID-19-associated intestinal damage. The following can be considered as the most probable ones: increased expression of angiotensin-converting enzyme 2 (ACE2) in enterocytes; disruption of autophagy mechanisms; pathological changes in gut microbiota; development of side effects of antiviral and antibacterial drugs. This review provides a systematic review of the molecular mechanisms of gastrointestinal damage, including the development of diarrheal syndrome in COVID-19 patients.